NUTRIAGEING: combining science, cooking and agriculture - Silva, M.S. (2016)
There are three main behavior traits that have been associated with human health status: to be physically active, to be mentally active and to eat well. These are the main topics addressed by PERSSILAA, an European Project focused on the development and validation of a new service model, to screen for and prevent frailty in older adults, integrating nutrition, physical and cognitive function. Nutrition plays an important role all over our life span, especially in older adults. The importance of nutrition education and the impact of consumer misinformation about the benefits of these food choices becomes clear with the recognition that nutritional status influences the rate of physiologic and functional decline with age. Helping people to choose more nutritive food that will contribute to maintain good health, improve their cognitive function, increase their energy levels and prevent their frailty. There are several available websites related to nutrition targeting the older adult population. However, some are not user friendly and eHealth literacy is still seen as a major obstacle to the uptake of ICT technologies in the health sector. The development of an interactive and user-friendly website providing information, advice and simple services focused on the nutritional status of elderly people, was a most needed task. The NUTRIAGEING website has emerged to address this need. It was created to be a major platform for the transfer of scientific knowledge into advice to the general public, integrated in the PERSSILAA platform. It will offer several modules to promote healthier nutrition, to educate the population on how to improve food habits, and on how to grow a vegetable garden. It will be structured around healthy eating, cooking recipes with videos, and vegetable gardens.